Digital Marketing Strategies and Service Quality on Purchase Decisions: The Role of Purchase Intention as a Mediator in MSMEs - Nining Farniati; Mahmud Mahmud; Ibrahim Zakariah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to empirically examine the effects of digital marketing strategy and service quality on purchasing decisions, using purchase intention as a mediating variable in a fashion MSME. Research Method: This explanatory quantitative study employed purposive sampling to select 97 active social media followers. Data were collected via online Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results and Discussion: Findings reveal that digital marketing directly and significantly influences purchasing decisions without building purchase intention. Conversely, service quality does not directly impact purchasing decisions; rather, it requires purchase intention as a full psychological mediator to generate real transactions. Implications: Fashion MSMEs should deploy aggressive digital marketing to drive quick sales conversions while simultaneously optimizing customer service quality to cultivate purchase intention for long-term engagement. Originality: This research resolves theoretical inconsistencies regarding the direct effects of digital marketing and service quality by integrating purchase intention as a psychological mediator in the highly dynamic digital fashion MSME sector.